A method for laser cladding on the surface of a gray cast iron brake disc

By directly performing laser cladding on the surface of gray cast iron brake discs and using multi-component rare earth doped nickel-based tungsten carbide alloy powder as the empowering alloy, the problem of pores and crack defects during laser cladding is solved, and the wear resistance of the brake discs is improved , corrosion resistance and service life.

CN114717549BActive Publication Date: 2025-02-18BEIJING NAT INNOVATION INST OF LIGHTWEIGHT LTD +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202210413907.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-14
Publication Date
2025-02-18
Estimated Expiration
2042-04-14

AI Technical Summary

Technical Problem

When laser cladding is performed on the surface of gray cast iron brake discs, defects such as pores and cracks are easily generated, which affects the bonding strength, wear resistance and corrosion resistance of the laser cladding layer and the substrate.

Method used

A laser cladding method that does not require pretreatment of gray cast iron matrix is ​​used to directly form a cladding layer without cracks and pores on the surface of gray cast iron brake discs, and use wear-resistant, corrosion-resistant and high-temperature-resistant multi-difficulty rare earth doping. Nickel-based tungsten carbide alloy powder is used as the empowering alloy.

Benefits of technology

The pores and crack defects in the laser cladding process of gray cast iron brake disc surface have been successfully eliminated, the hardness, wear resistance and corrosion resistance of the surface have been improved, and the service life of the brake disc has been extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114717549B_ABST
    Figure CN114717549B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of laser beam processing technology, and may also relate to the processing of metal powders, and in particular to a method for laser cladding on the surface of a gray cast iron brake disc. The difference from the prior art is that: there is no need to perform pre-treatment work such as sandblasting, preheating, and pre-setting a base layer on the gray cast iron substrate, and the energized alloy powder is directly used through laser cladding technology to form one or more cladding layers with good metallurgical bonding on the surface of the gray cast iron brake disc. Compared with the prior art, the present invention does not require pre-treatment work such as sandblasting, preheating, and pre-setting a base layer before cladding, and is a low-energy, fast cladding method; it successfully eliminates defects such as pores and cracks that are easily generated during the cladding process; it improves the hardness, wear resistance, and corrosion resistance of the surface of the gray cast iron brake disc; and it improves the reliability and service life of the gray cast iron brake disc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of laser beam processing, and may also relate to the processing of metal powder, and in particular to a method for laser cladding on the surface of a gray cast iron brake disc. Background Art

[0002] Gray cast iron material has the characteristics of high shock absorption, excellent thermal conductivity, good processability and low cost, and is widely used in the production and manufacturing of brake discs. However, gray cast iron material still has certain defects, such as low strength, poor wear resistance and corrosion resistance. In actual use, the brake disc is prone to wear and corrosion on the surface due to the combined effects of mechanical loads, thermal loads and high-temperature oxidation, which reduces the safety and reliability of the brake disc. How to modify the surface of gray cast iron brake discs to improve their wear resistance and corrosion resistance, so as to avoid premature failure of gray cast iron brake discs and extend their service life is one of the research and development directions in this field.

[0003] Laser cladding is an advanced surface modification technology. It uses a high-energy-density laser beam to rapidly melt and solidify the alloy material added to the substrate surface and the thin layer on the substrate surface, forming a coating with special functions and low dilution rate and metallurgically bonded to the substrate, so that the substrate surface has excellent properties such as wear resistance, corrosion resistance, heat insulation, insulation and oxidation resistance. However, when laser cladding technology is applied to the substrate of gray cast iron materials, the high carbon content of graphite in the gray cast iron matrix reduces the plastic toughness of the matrix, and the weldability of the gray cast iron material is extremely poor. When laser cladding powder with high temperature resistance, wear resistance, and corrosion resistance is performed on the surface of the gray cast iron brake disc, the gray cast iron brake disc substrate and the laser cladding layer are prone to cracks and pores during the rapid solidification and cooling process, which seriously affects the bonding strength, wear resistance, and corrosion resistance of the laser cladding layer and the gray cast iron brake disc substrate, and reduces the reliability of the laser cladding technology on the surface of the gray cast iron brake disc. Therefore, how to use the laser cladding process is to improve the surface performance of the gray cast iron brake disc. The existing technology has not yet made any significant breakthrough in this regard. Summary of the invention

[0004] In order to solve the defects such as pores and cracks that are easily generated in the process of directly laser cladding a wear-resistant and corrosion-resistant enabling layer on the surface of gray cast iron, the present invention provides a method for laser cladding on the surface of a gray cast iron brake disc, thereby avoiding the defects such as pores and cracks generated by the gray cast iron during the laser cladding process, improving the wear resistance, corrosion resistance and high temperature resistance of the surface of the gray cast iron brake disc, and extending the service life of the gray cast iron brake disc.

[0005] The technical solution adopted by the present invention is:

[0006] A method for laser cladding on the surface of a gray cast iron brake disc, which is different from the prior art in that: there is no need to perform pretreatment work such as sandblasting, preheating and pre-setting a base layer on the surface of the gray cast iron substrate, and the empowered alloy powder is directly used through laser cladding technology to form one or more cladding layers without metallurgical defects such as cracks and pores on the surface of the gray cast iron brake disc substrate.

[0007] Preferably, the empowering alloy powder is a wear-resistant, corrosion-resistant and high-temperature resistant multi-rare earth-doped nickel-based tungsten carbide alloy powder, and the empowering alloy powder is composed of the following raw materials in percentage by mass: 0.2% to 1.5% C, 15 to 45% WC, 0.5% to 3.5% Mo, 1.5 to 8% Fe, 0.1 to 0.5% Si, 0.1 to 1.5% Ti, 0.1% to 0.8% CeO2, 0.1% to 1.2% Y2O3, 0.1% to 1.2% La2O3 and the remainder Ni.

[0008] Preferably, the particle size of the energized alloy powder is 150-300 mesh, the oxygen content is ≤200 ppm, the nitrogen content is ≤200 ppm, and the fluidity is ≤20 (s / 50 g).

[0009] Preferably, before laser cladding the energized alloy powder, the surface of the gray cast iron brake disc substrate at the location to be clad is polished with a grinding wheel to a metallic luster, and the surface contaminants such as oil and water are wiped clean with alcohol.

[0010] Preferably, the powder feeding nozzle for laser cladding on the surface of the gray cast iron brake disc substrate is a coaxial annular powder feeding nozzle or a 4-beam coaxial powder feeding nozzle, the laser spot diameter is 1 to 6 mm, the shielding gas is argon, and the shielding gas flow rate is 15 to 25 L / min.

[0011] Preferably, the laser cladding process parameters of the energized alloy powder are: laser power of 900-1500 W, scanning speed of 10-40 mm / s, powder feeding speed of 10-20 g / min, overlap rate of 60-80%, and single-layer cladding thickness of 0.3-1.2 mm.

[0012] Preferably, after laser cladding the energized alloy powder, the gray cast iron brake disc substrate is kept warm and slowly cooled to room temperature.

[0013] Preferably, after the temperature drops to room temperature, the surface of the laser cladding layer of the gray cast iron brake disc substrate is subjected to penetrant testing.

[0014] Compared with the prior art, the present invention has the following beneficial technical effects:

[0015] It is a low-energy and fast laser cladding method that does not require pre-treatment work such as sandblasting, preheating and pre-setting of the base layer before laser cladding of the energy layer. It successfully eliminates defects such as pores and cracks that are easily generated during the laser cladding process on the surface of the gray cast iron brake disc; improves the hardness, wear resistance and corrosion resistance of the surface of the gray cast iron brake disc; and improves the reliability and service life of the gray cast iron brake disc. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 It is a schematic diagram of the hierarchical structure of a gray cast iron substrate after laser cladding of the present invention;

[0017] Figure 2 is a nondestructive testing photograph of the HT250 gray cast iron brake disc of Example 1 after laser cladding by the method of the present invention;

[0018] Figure 3 is a cross-sectional metallographic photograph of the HT250 gray cast iron brake disc of Example 1 on which a laser cladding layer is formed by the method of the present invention;

[0019] Figure 4 is a cross-sectional hardness curve of a laser cladding layer formed on a HT250 grey cast iron brake disc of Example 1 by the method of the present invention;

[0020] Figure 5 is a wear performance test curve of the HT250 gray cast iron brake disc of Example 1 formed with a laser cladding layer by the method of the present invention;

[0021] Figure 6 This is a penetrant flaw detection photograph of the HT250 gray cast iron brake disc of Example 1 after laser cladding by the traditional method;

[0022] Figure 7 is a nondestructive testing photograph of the HT300 grey cast iron brake disc of Example 2 after laser cladding by the method of the present invention;

[0023] Figure 8 is a cross-sectional metallographic photograph of the HT300 grey cast iron brake disc of Example 2, in which a laser cladding layer is formed by the method of the present invention;

[0024] Fig. 9 is a cross-sectional hardness curve of a laser cladding layer formed on the HT300 grey cast iron brake disc of Example 2 by the method of the present invention;

[0025] Fig.10 is a wear performance test curve of the HT300 grey cast iron brake disc of Example 2 formed with a laser cladding layer by the method of the present invention;

[0026] Fig.11 This is a penetrant inspection photograph of the HT300 gray cast iron brake disc of Example 2 after laser cladding using the traditional method.

[0027] Reference numerals:

[0028] 1—Gray cast iron matrix; 2—Energy-enabling layer; 3—Reinforcement phase. DETAILED DESCRIPTION

[0029] The present invention will be further described below in conjunction with the accompanying drawings.

[0030] Figure 1 The figure schematically shows the structure of the gray cast iron laser cladding layer involved in the present invention. Figure 1 The structure of the laser cladding enabling layer is only given for illustration. The multi-component rare earth doped nickel-based alloy 2 is the metal matrix of the enabling layer, which can be one layer or multiple layers. The tungsten carbide particles 3 are the strengthening phases, and the quantity, size and shape can be selected according to actual needs.

[0031] Embodiment 1:

[0032] The surface of the HT250 gray cast iron brake disc is polished with a grinding wheel to a metallic luster, and the oil, water and other dirt on the surface are wiped clean with alcohol;

[0033] A wear-resistant, corrosion-resistant and high-temperature resistant multi-rare earth-doped nickel-based tungsten carbide alloy powder was selected as an enabling layer for laser cladding on the surface of an HT250 gray cast iron brake disc. The enabling alloy powder was composed of the following raw materials in percentage by mass: 1.2% C, 25% WC, 2.3% Mo, 6.0% Fe, 0.3% Si, 1.2% Ti, 0.5% CeO2, 0.8% Y2O3, 0.8% La2O3 and the remainder Ni.

[0034] The particle size of the energized alloy powder is 150-270 mesh, oxygen content = 196 ppm, nitrogen content = 173 ppm, and fluidity = 18 (s / 50 g).

[0035] The powder feeding nozzle for laser cladding on the surface of the gray cast iron brake disc substrate is a coaxial annular powder feeding nozzle, the laser spot diameter is 3 mm, the shielding gas is argon, and the shielding gas flow rate is 18 L / min.

[0036] The laser cladding process parameters of the energized alloy powder are: laser power: 1100 W, scanning speed: 20 mm / s, powder feeding speed: 15 g / min, overlap rate: 65%, cladding layer thickness 0.6 mm;

[0037] The HT250 gray cast iron brake disc after cladding is kept warm and slowly cooled. After it drops to room temperature, the surface of the cladding layer is subjected to penetrant testing. Figure 2 As shown in the figure, no defects such as pores and cracks were found on the surface of the cladding layer.

[0038] The HT250 gray cast iron brake disc after cladding was sampled and metallographic observation was performed. Figure 3 As shown in the figure, a good metallurgical bond is formed between the laser cladding energy layer and the gray cast iron HT250 substrate, the tungsten carbide particles are highly dispersed in the metal matrix, and no obvious defects such as pores and cracks are found in the cross section of the cladding layer.

[0039] The HT250 grey cast iron brake disc after cladding was sampled and subjected to cross-sectional hardness test. The results are as follows: Figure 4 As shown, the hardness of the HT250 substrate is about 220-260 Hv, the hardness of the energy-empowering layer substrate is about 400-450 Hv, and the hardness of the tungsten carbide particles is about 2500-2700 Hv.

[0040] The wear performance test results of the HT250 gray cast iron brake disc after cladding are as follows: Figure 5 As shown in the figure, the wear loss of the laser cladding energy layer is about 20% of the HT250 substrate, which significantly improves the wear resistance and reliability of the HT250 gray cast iron brake disc surface.

[0041] Comparative Example 1:

[0042] The surface of the HT250 gray cast iron brake disc is polished with a grinding wheel to a metallic luster, and the oil, water and other dirt on the surface are wiped clean with alcohol;

[0043] Nickel-based tungsten carbide alloy powder was selected as the enabling layer for laser cladding on the surface of HT250 gray cast iron brake disc. The enabling alloy powder consisted of the following raw materials in mass percentage: 1.2% C, 25% WC, 2.3% Mo, 6.0% Fe, 0.3% Si and the remainder Ni.

[0044] The particle size of the energized alloy powder is 150-270 mesh, oxygen content = 196 ppm, nitrogen content = 173 ppm, and fluidity = 18 (s / 50 g).

[0045] The powder feeding nozzle for laser cladding on the surface of the gray cast iron brake disc substrate is a coaxial annular powder feeding nozzle, the laser spot diameter is 3 mm, the shielding gas is argon, and the shielding gas flow rate is 18 L / min.

[0046] The laser cladding process parameters of the energized alloy powder are: laser power: 1100 W, scanning speed: 20 mm / s, powder feeding speed: 15 g / min, overlap rate: 65%, cladding layer thickness 0.6 mm;

[0047] The HT250 gray cast iron brake disc after cladding is kept warm and slowly cooled. After it drops to room temperature, the surface of the cladding layer is subjected to penetrant testing. Figure 6 As shown in the figure, pores and cracks were found on the surface of the laser cladding layer.

[0048] In this comparative example 1, no rare earth element and Ti element are doped between the energy-enabling layer and the HT250 substrate. Therefore, the doping of rare earth element and Ti element does not produce the impurity removal and stabilization effect on the graphite phase of the gray cast iron HT250 substrate after thermal decomposition. Therefore, it cannot effectively reduce the carbon monoxide gas generated by the reaction of carbon and oxygen during the laser cladding process. Figure 6 As shown in the figure, the laser cladding energy-enhancing layer on the surface of the gray cast iron HT250 brake disc produces two transverse cracks and several obvious defects such as pores.

[0049] Embodiment 2:

[0050] The surface of the HT300 gray cast iron brake disc is polished with a grinding wheel to a metallic luster, and the oil, water and other dirt on the surface are wiped clean with alcohol;

[0051] A wear-resistant, corrosion-resistant and high-temperature resistant multi-rare earth-doped nickel-based tungsten carbide alloy powder was selected as an enabling layer for laser cladding on the surface of an HT300 gray cast iron brake disc. The enabling alloy powder was composed of the following raw materials in percentage by mass: 0.8% C, 30% WC, 2.8% Mo, 6% Fe, 0.3% Si, 1.2% Ti, 0.3% CeO2, 0.6% Y2O3, 0.8% La2O3 and the remainder Ni.

[0052] The particle size of the energized alloy powder is 150-270 meshes, the oxygen content is 190 ppm, the nitrogen content is 180 ppm, and the fluidity is 18 (s / 50 g).

[0053] The powder feeding nozzle for laser cladding on the surface of the gray cast iron brake disc substrate is a 4-beam coaxial powder feeding nozzle, the laser spot diameter is 4.2 mm, the shielding gas is argon, and the shielding gas flow rate is 22 L / min.

[0054] The laser cladding process parameters of the energized alloy powder are: laser power: 1350 W, scanning speed: 30 mm / s, powder feeding speed: 23 g / min, overlap rate: 63%, cladding layer thickness 0.8 mm;

[0055] The HT300 gray cast iron brake disc after cladding is kept warm and slowly cooled. After it drops to room temperature, the surface of the cladding layer is subjected to penetrant testing. Figure 7 As shown in the figure, no defects such as pores and cracks were found on the surface of the cladding layer.

[0056] The HT300 gray cast iron brake disc after cladding was sampled and metallographic observation was performed. Figure 8 As shown in the figure, a good metallurgical bond is formed between the laser cladding enabling layer and the gray cast iron HT300 substrate, the tungsten carbide particles are highly dispersed in the metal matrix, and no obvious defects such as pores and cracks are found in the cross section of the cladding layer.

[0057] The HT300 grey cast iron brake disc after cladding was sampled and subjected to cross-sectional hardness test. The results are as follows: Fig. 9 As shown, the hardness of the HT300 substrate is about 230-270 Hv, the hardness of the energy-empowering layer substrate is about 400-450 Hv, and the hardness of the tungsten carbide particles is about 2200-2500 Hv.

[0058] The wear performance test results of the HT300 gray cast iron brake disc after cladding are as follows: Fig.10 As shown in the figure, the wear loss of the laser cladding energy layer is about 18% of the HT300 substrate, which significantly improves the wear resistance and reliability of the HT300 gray cast iron brake disc surface.

[0059] Comparative Example 2:

[0060] The surface of the HT300 gray cast iron brake disc is polished with a grinding wheel to a metallic luster, and the oil, water and other dirt on the surface are wiped clean with alcohol;

[0061] Nickel-based tungsten carbide alloy powder was selected as the enabling layer for laser cladding on the surface of HT300 gray cast iron brake disc. The enabling alloy powder consisted of the following raw materials in mass percentage: 0.8% C, 30% WC, 2.8% Mo, 6% Fe, 0.3% Si and the balance Ni.

[0062] The particle size of the energized alloy powder is 150-270 meshes, the oxygen content is 190 ppm, the nitrogen content is 180 ppm, and the fluidity is 18 (s / 50 g).

[0063] The powder feeding nozzle for laser cladding on the surface of the gray cast iron brake disc substrate is a 4-beam coaxial powder feeding nozzle, the laser spot diameter is 4.2 mm, the shielding gas is argon, and the shielding gas flow rate is 22 L / min.

[0064] The laser cladding process parameters of the energized alloy powder are: laser power: 1350 W, scanning speed: 30 mm / s, powder feeding speed: 23 g / min, overlap rate: 63%, cladding layer thickness 0.8 mm;

[0065] The HT300 gray cast iron brake disc after cladding is kept warm and slowly cooled. After it drops to room temperature, the surface of the cladding layer is subjected to penetrant testing. Fig.11 As shown in the figure, pores and cracks were found on the surface of the laser cladding layer.

[0066] In this comparative example 1, no rare earth element and Ti element are doped between the energy-enabling layer and the HT300 substrate. Therefore, the doping of rare earth element and Ti element does not produce the impurity removal and stabilization effect on the graphite phase of the gray cast iron HT300 substrate after thermal decomposition. Therefore, it cannot effectively reduce the carbon monoxide gas generated by the reaction of carbon and oxygen during the laser cladding process. Fig.11As shown in the figure, the laser cladding energy-enhancing layer on the surface of the gray cast iron HT300 brake disc produces obvious defects such as a transverse crack and several pores.

[0067] Through the laser cladding method for the surface of a gray cast iron brake disc of the present invention, a good metallurgical bond is formed between the laser cladding enabling layer and the gray cast iron substrate, and the cladding layer formed on the surface of the gray cast iron brake disc is free of metallurgical defects such as pores and cracks, thereby improving the surface hardness, wear resistance, corrosion resistance and other comprehensive properties of the gray iron brake disc, thereby improving the reliability and service life of the gray iron brake disc.

[0068] The above embodiments are provided only for the purpose of describing the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various changes and modifications. Any modifications made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for laser cladding on the surface of a gray cast iron brake disc, characterized in that: There is no need to perform pretreatment work such as sandblasting, preheating and pre-setting a base layer on the surface of the gray cast iron brake disc substrate (1), and the empowered alloy powder (2) is directly used to form one or more cladding layers without metallurgical defects such as cracks and pores on the surface of the gray cast iron brake disc substrate (1) through laser cladding technology; the empowered alloy powder (2) is a multi-component rare earth-doped nickel-based tungsten carbide alloy powder that is wear-resistant, corrosion-resistant and high-temperature resistant; the empowered alloy powder (2) is composed of the following raw materials in percentage by mass: 0.2% to 1.5% C, 15 to 45% WC, 0.5% to 3.5% Mo, 1.5 to 8% Fe, 0.1 to 0.5% Si, 0.1 to 1.2% Ti, 0.1% to 0.8% CeO2, 0.1% to 1.2% Y2O3, 0.1% to 1.2% La2O3 and the remainder Ni.

2. The method for laser cladding on the surface of a gray cast iron brake disc according to claim 1, characterized in that: The particle size of the energized alloy powder (2) is 150-300 meshes, the oxygen content is ≤200ppm, the nitrogen content is ≤200PPm, and the fluidity is ≤20 (s / 50g).

3. The method for laser cladding on the surface of a gray cast iron brake disc according to claim 1, characterized in that: Before laser cladding the energized alloy powder (2), the surface of the gray cast iron brake disc substrate (1) at the location to be clad is polished with a grinding wheel to a metallic luster, and the surface is cleaned of oil, water and other dirt with alcohol.

4. The method for laser cladding on the surface of a gray cast iron brake disc according to claim 1, characterized in that: The powder feeding nozzle for laser cladding on the surface of the gray cast iron brake disc substrate (1) is a coaxial annular powder feeding nozzle or a 4-beam coaxial powder feeding nozzle, the laser spot diameter is 1 to 6 mm, the shielding gas is argon, and the shielding gas flow rate is 15 to 25 L / min.

5. The method for laser cladding on the surface of a gray cast iron brake disc according to claim 1, characterized in that: The laser cladding process parameters of the energized alloy powder (2) are: laser power of 900-1500W, scanning speed of 10-40mm / s, powder feeding speed of 10-25g / min, overlap rate of 60-80%, and single-layer cladding thickness of 0.3-1.2mm.

6. The method for laser cladding on the surface of a gray cast iron brake disc according to claim 1, characterized in that: After laser cladding of the energized alloy powder (2), the gray cast iron brake disc substrate (1) is kept warm and slowly cooled to room temperature.

7. The method for laser cladding on the surface of a gray cast iron brake disc according to claim 1, characterized in that: After the temperature drops to room temperature, a penetration test is performed on the surface of the laser cladding layer of the gray cast iron brake disc substrate (1).

Citation Information

Cited By

  • Preparation method for laser cladding of iron-based alloy wear-resistant coating on surface of automobile brake disc

    CN120666330A

  • Sand blasting derusting device for automobile brake disc machining

    CN224144360U